JSE 29:4 Winter Editorial - Braude, Stephen (Journal of Scientific Exploration, 2015)
In the Summer 2014 JSE issue (Volume 28:2), we published two long reports, by Michael Nahm and myself, on the investigation of physical medium Kai Mügge and the Felix Circle. Those papers were revised versions of papers, ready to be published earlier, but scuttled when evidence of fraud was uncovered in the case. Nahm and I reached different conclusions about Kai’s mediumship as a whole. He felt that the majority of Kai’s phenomena were probably fraudulent. I was not ready to go that far. In any case, whatever our intuitions might have been about the extent of Kai’s cheating, we both agreed that some of his phenomena were still very difficult to explain away—and indeed had not been adequately explained away. I believe it’s fair to say that however large or small that residue of legitimacy may be, Nahm and I agree that it at least includes table levitations. Since that JSE issue was published, there have been further developments in the case. Some of these, from an investigation I supervised in October of this year, I hope to present at length in a future issue of the JSE. The rest concern some incidents that occurred relatively soon after the appearance of our original reports, and which should be mentioned now without further ado. The item of greatest interest, no doubt, will be the testimony—quoted below—describing how at least one instance of Kai’s cheating was uncovered.